Implications of gas scarcity for European energy policy - Daniel Gros (EconPol Forum, 2022)
The global supply of natural gas is fixed in the short run. Europe can replace the missing Russian gas only by bidding more than consumers elsewhere, especially in Asia, are willing to pay. The supply of gas available for Europe is thus highly inelastic; therefore, the marginal cost is an order of magnitude higher than the price. Consumers do not factor this externality in their decisions. They should be given extra incentives to save. Individual countries will engage in insufficient gas-saving efforts because they do not take into account that their national gas savings will benefit all their partners through lower import prices. EU policy should concentrate on ways to save gas, not on how consumers are protected from the current high prices
Keywords: 330